Penerapan Sistem Pendukung Keputusan untuk Seleksi Kelayakan Rekomendasi Penerima Beasiswa Kip dengan Metode Moora (Studi Kasus : SMK Kesehatan Nusantara Sorong) - Hamila Rumodar; Nur Miswar; Muh. Fadli Hasa (Universitas Muhammadiyah Sorong, 2024)
One of the problems faced by the Indonesian government in the field of education is the equalization of education from Sabang to Merauke in providing quality and superior education. In overcoming this, the Indonesian government runs a program called PIP (Smart Indonesia Program). PIP is a cash assistance program for education aimed at school-age children between 6 and 21 years old who have a low-income economic background so that they can experience fair and equal education services. A person who receives PIP will be given a marker card called the Smart Indonesia Card (KIP). Each educational unit or school has the right to propose students to receive PIP/KIP scholarships through the local Education Office. SMK Kesehatan Nusantara Sorong carries out the selection process for the eligibility of students for the proposal of PIP/KIP recipients which is still done subjectively and manually so that a solution is needed to reduce negative impacts such as not being on target, inefficient time and not being computerized. A decision support system can be applied to overcome these problems. DSS is built by implementing the RAD development method, the MOORA DSS method and the Black Box testing method and Usability Testing. The results of the selection process for the eligibility of PIP/KIP scholarship recipient recommendations on sample data are 20 alternatives with the highest ranking values, namely students 63, 12, 35, 55, 50, 57, 15, 23, 67, 28, 62, 40, 44, 9, 39, 8, 19, 29, 45, and 3 with the highest ranking value of 0.1285. The results of this study are a system that can be used to carry out the selection process for the eligibility of students for recommendations for PIP/KIP scholarship recipients.